The (non) sense of organizational change: an Essai about universal management hypes, sick consultancy metaphors, and healthy organization theories - Sorge, Arndt; Witeloostuijn (2004)
The global business world is infected by a virus that induces a permanent need for organizational change, which is fed by the management consultancy industry. The nature of the organizational change hype changes colour frequently, through the emergence of new universal management fashions. an urge to change is understandable from the perspectives of the consultant and the manager, but often organizational changes are ineffective or counter-productive when implemented. In this context, this article's purpose is threefold. First, on the basis of an interpretation of different literatures, we flesh out an argument about the nonsense of organizational change that is driven by sick consultancy metaphors. Second, we argue that the application of healthy organization theories offers ample guidelines for organizational change initiatives that make more sense than prominent management consultancy rhetoric. Third, pulling both strings together, we plead for the development of an evidence-based (change) consultancy practice. - Reproduced.
Keywords: Management; Organizational change